MODERN SATELLITE NAVIGATION SYSTEM AS A FORM OF INFORMATSIONNOY COMPETENCE OF FUTURE SUDOVODITELEY (Journal of Information Technologies in Education (ITE), 2012)
In given article the essence of application and a principle of action of satellite systems of navigation existing for today and their application in with-time navigation, and as in the course of preparation of navigators is considered.
Keywords: BeiDou; DGPS; Galileo; GPS; IRNSS; location of the vessel; NAVSTAR; Satellite system of navigation; ГЛОНАСС